Comorbidities of self‐reported fibromyalgia in United States adults: A cross‐sectional study from The National Epidemiological Survey on Alcohol and Related Conditions (NESARC‐III). (18th May 2020) - Sleurs, David; Tebeka, Sarah; Scognamiglio, Claire; Dubertret, Caroline; Le Strat, Yann
Abstract: Background: Fibromyalgia has been associated with various physical and mental disorders. However, these comorbidities need to be quantified in a population‐based study. Method: We compared participants with and without self‐reported fibromyalgia to assess (a) The prevalence of self‐reported fibromyalgia and its sociodemographic characteristics in a US representative sample, (b) The associations between self‐reported fibromyalgia and lifetime and past 12‐month mental and physical disorders and (c) The quality of life associated with self‐reported fibromyalgia. This cross‐sectional study used a large national sample ( n = 36, 309) of the US population, the National Epidemiologic Survey on Alcohol and Related Conditions‐III. Face to face interviews were conducted, collecting sociodemographic characteristics, diagnostic and statistical manual of mental disorders‐5 structured diagnosis and self‐reported medical conditions (including fibromyalgia). Results: The past 12‐month prevalence of self‐reported fibromyalgia was estimated at 2.05%. Participants with self‐reported fibromyalgia were significantly at higher risk to report a lifetime history of mental disorder (adjusted odds ratio [aOR] = 2.32). Self‐reported fibromyalgia was also positively associated with 24 of the 27 physical conditions assessed in this study. Participants with self‐reported fibromyalgia were more likely to report a past 12‐month history of suicide attempts (aOR = 5.81), substance use disorders (aOR = 1.40), mood disorders (aOR = 2.67), anxiety disorders (aOR = 2.75) and eating disorders (aOR = 2.45). Participants with self‐reported fibromyalgia had lower levels of both mental and physical quality of life than those without fibromyalgia. Conclusions: Participants with self‐reported fibromyalgia have a higher prevalence of comorbid mental and physical disorders, and lower mean levels of mental and physical quality of life than their counterparts without fibromyalgia. Significance: We showed here a strong association of self‐reported fibromyalgia with both mental and physical comorbidities. We showed that among participants with self‐reported fibromyalgia, more than 8 out of 10 had at least three other physical comorbidities, and almost half had at least three mental comorbidities. This is a cross‐sectional study using a representative sample of the US population with highly reliable psychiatric diagnosis that makes our results generalizable. Practitioners managing fibromyalgia should search and treat these comorbidities.